Exploring Digital-Based Adaptive Leadership in Supporting the Implementation of Deep Learning in the Independent Curriculum in the Era of Society 5.0 - Rosnelli Rosnelli; Dadang Mulyana; Yuniarto Mudjisusatyo; Arif Rahman; Darwin Darwin (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
This study aims to analyze the role of digital-based adaptive leadership in supporting deep learning in the Merdeka Curriculum in the Society 5.0 era. The method used is descriptive qualitative with junior high and senior high school teachers in Deli Serdang Regency selected purposively. Data were collected through interviews, observation, and documentation, then analyzed using an interactive model. The results show that digital-based adaptive leadership has been implemented through policies, training, and technology provision, but has not been optimal due to the digital literacy gap among teachers. Supporting factors include a culture of innovation, leadership support, and infrastructure, while the main obstacle is the low digital competence of some teachers. It is concluded that this leadership plays a strategic role, but requires continuous and needs-based teacher capacity building.